2021
DOI: 10.2147/ceor.s306823
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cost-Effectiveness of Iron Formulations for the Treatment of Iron Deficiency Anaemia in Patients with Inflammatory Bowel Disease in the UK

Abstract: Introduction In patients with inflammatory bowel disease (IBD), iron deficiency anaemia (IDA) can impair quality of life and increase healthcare costs. Treatment options for IDA-associated IBD include oral iron and intravenous iron formulations (such as ferric carboxymaltose [FCM], ferric derisomaltose [FD, previously known as iron isomaltoside 1000], and iron sucrose [IS]). The present analysis compared the cost-effectiveness of FCM versus FD, IS, and oral iron sulfate in terms of additional cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Their multifactorial etiopathogenesis has not been clearly defined to date. They include, among others, immunological background, genetic, and environmental factors [1,2].…”
Section: Introduction 1inflammatory Bowel Diseasementioning
confidence: 99%
“…Their multifactorial etiopathogenesis has not been clearly defined to date. They include, among others, immunological background, genetic, and environmental factors [1,2].…”
Section: Introduction 1inflammatory Bowel Diseasementioning
confidence: 99%
“…Model projections were limited to a 1-year time horizon, meaning that outcomes were not discounted. The underlying model has previously been published by Aksan et al for similar calculations of the cost per responder in the Swiss and UK national settings [25,26] but was restructured to meet the scope of this study, in the Swedish regional setting.…”
Section: Methodsmentioning
confidence: 99%
“…A CEA of FD vs. FCM in the UK found that haematological response was 9% higher in patients treated with FD than with FCM [24]. On the other hand, two separate analyses of FCM vs. FD and IS in Switzerland and the UK estimated that, in terms of costeffectiveness, FCM was both more effective and less costly for the respective health-care systems [25,26]. In the Nordic context, a 2018 economic evaluation of FD vs. FCM was conducted in the Danish setting, followed by another economic evaluation in 2021, which used data for patients in Norway, Sweden, and Denmark.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been evaluations of the cost-effectiveness of different iron therapies in patients with IDA, [26][27][28][29] we are unaware of any such analyses specifically in the context of acute GIB-related ID/IDA. Delays in the administration of iron replacement are common and likely impact both direct medical costs and indirect costs in terms of the negative effect on the patient's QoL and productivity losses.…”
Section: Cost-effectiveness Of Different Iron Therapiesmentioning
confidence: 99%